2019
DOI: 10.26719/emhj.18.057
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, control and risk factors related to hypertension among Moroccan adults: a multicentre study

Abstract: Background: Hypertension is a leading risk factor for mortality and morbidity. Aims: The objective of this study was to determine the prevalence and clinical profile of hypertension in a large sample of individuals in Morocco. Methods: This was a multicentre and cross-sectional study conducted on patients consulting primary care physicians in Morocco between 2008 and 2009. Data were collected via a medical examination and a questionnaire covering patient demographics, medical history and cardiovascular risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…[11] This rate was better than the 17.1% reported in a study carried out in Morocco and was comparable to the 37.0%, 39.0%, and 45.3% figures reported in studies conducted in Ethiopia, Europe, and Sudan, respectively. [14151819] However, BP control was lower in this study than that has been reported in the studies conducted in developed countries such as the US (64.0%) and Canada (66.0%). [2021] Disparities encountered in the findings of these studies were related to the difference in the thresholds used to define BP control, in addition to the differences in the study populations, and health-care systems.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…[11] This rate was better than the 17.1% reported in a study carried out in Morocco and was comparable to the 37.0%, 39.0%, and 45.3% figures reported in studies conducted in Ethiopia, Europe, and Sudan, respectively. [14151819] However, BP control was lower in this study than that has been reported in the studies conducted in developed countries such as the US (64.0%) and Canada (66.0%). [2021] Disparities encountered in the findings of these studies were related to the difference in the thresholds used to define BP control, in addition to the differences in the study populations, and health-care systems.…”
Section: Discussioncontrasting
confidence: 72%
“…Despite the wide availability of safe and effective treatment, BP control remains suboptimal in many countries. [171819] Adherence may play a significant role, as some patients may only take their antihypertensive medications when they experience certain symptoms. [29] Alternatively, patients may opt to stop their medication on experiencing initial side effects such as increased urination with diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…It is more prevalent in low-and middle-income countries (31.5%) than higherincome (28.5%). 5 The prevalence of hypertension is 40.41% in Romania, 6 39.8% in Morocco, 7 28.1% in Ghana, 8 26.4% in Uganda, 9 23% in Northern Angola, 10 20.5% in southern China, 11 and 17% in India. 12 Hypertension is also dramatically increasing in Ethiopia, particularly in urban communities.…”
Section: Introductionmentioning
confidence: 99%
“…However, high potassium consumption can counteract the negative effects of high sodium intake on blood pressure. Potassium therefore plays a protective role, in lowering blood pressure [3]. WHOs report highlights the importance of prioritizing the reduction of sodium intake as the primary approach to reducing blood pressure and reducing the risk of stroke and CVDs [4].…”
Section: Introductionmentioning
confidence: 99%